(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Microorganisms are the causative agent for infective diseases, food spoilage and food borne diseases. Drug resistance and use of chemical preservatives have currently reduced the safety of food products in food industry. Therefore, there is an urgent need for the discovery of antimicrobial agents that could overcome this shortage.